Misérias das fronteiras: exploração sexual; crianças e adolescentes femininas em Foz do Iguaçu - Maia, Lucia Maria Andrade (2012)
The present work investigates the social, economical, political, cultural and historical aspects that make children and adolescents vulnerable to sexual exploitation in the City of Iguassu, state of Paraná, Brazil. The large number of children and adolescents in situation of sexual exploitation worldwide, in Brazil and in Iguassu is sufficient to justify this study theme. The border's miseries , the sexual exploitation of female children and adolescents in Iguassu has the purpose to understand the qualitative details of sexual exploitation on female children and adolescents in Iguassu, Brazil, in 2012. We aim at finding the characteristics of this context, and understand, through studies, documents, descriptions and narratives, the sexual exploitation, and identify its characterictics and specificities. We have given priviledge to field research, by means of auscultation techniques, which consist in collecting free testimonials, allowing the subjects of the research to report their own lives. Throughout the auscultation we have found dramatic stories of the people who had their lives violated by social miseries, sexual abuse and exploitation.